2022
DOI: 10.3389/fmed.2022.860644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Outcomes of Renal Transplantation Patients With Pneumocystis jirovecii Pneumonia and Cytomegalovirus Co-infection

Abstract: BackgroundPneumocystis jirovecii pneumonia (PJP) and cytomegalovirus (CMV) infection are common opportunistic infections among renal transplantation (RT) recipients, and both can increase the risk of graft loss and patient mortality after RT. However, few studies had evaluated PJP and CMV co-infection, especially among RT patients. Therefore, this study was performed to evaluate the impact of CMV co-infection with PJP among RT recipients.MethodsWe retrospectively analyzed the clinical data of patients with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…The sensitivity of hypoalbuminemia was more than 90% in ROC analysis. Previous studies suggested that hypoalbuminemia was associated with lung injury and serum albumin was an important independent factor for poor prognosis in HIV patients infected with PJP 2,37 . Hypoalbuminemia means poor nutrition status and the amount of immune globulins might be lowered, which might affect the immune function of the human body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity of hypoalbuminemia was more than 90% in ROC analysis. Previous studies suggested that hypoalbuminemia was associated with lung injury and serum albumin was an important independent factor for poor prognosis in HIV patients infected with PJP 2,37 . Hypoalbuminemia means poor nutrition status and the amount of immune globulins might be lowered, which might affect the immune function of the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocystis jirovecii pneumonia (PJP), an opportunistic infection that is sometimes life-threatening, often occurs in individuals with impaired immunity. 1,2 Severe cases can develop respiratory failure and even die. 3,4 It initially attracted attention among human immunodeficiency virus (HIV) patients, 5 then in solid organ transplantation recipients, haematopoietic stem cell transplantation patients, and those who received corticosteroids and chemotherapy drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [5] found that decreased lymphocyte counts, and high doses of steroid administration were associated with in-hospital mortality of PCP. Additionally, there is accumulating evidence [21][22][23] indicating that PCP always co-infect with other pathogens. NLR can be regarded as a convenient index to re ect the integrated lymphocyte level adjusted by neutrophil to estimate the severity of PCP.…”
Section: Discussionmentioning
confidence: 99%